ANALISIS KINERJA KEUANGAN PADA UD. VICKO DI KOTA SAMARINDA TAHUN 2014-2016 - Puspa Rini, Yunita Diyah (EKONOMIA, 2019)
The purpose of this study was to determine the development of financial performance at UD. Vicko in Samarinda in terms of liquidity ratios, solvency ratios and profitability ratios based on 2014 financial report data up to 2016.The basic theory used is financial management. Financial management is all the activities of companies that are related to businesses to obtain funds and allocate funds efficiently. Â Analysis tools use financial statements in the form of balance sheets and profit and loss. In addition to using a measuring instrument that is the liquidity ratio (current ratio) solvency ratio (debt to asset ratio) and profitability ratio (return on assets). The results showed: UD financial performance. Vicko in terms of liquidity ratios (current assets) decreased by 40.20% in 2015 and 11.88% in 2016. The solvency ratio in terms of the debt to asset ratio increased by 5.17% in 2015 and 4., 69% in 2016. Rentability ratio in terms of return on assets decreased by 4.12% in 2015 and 1.09% in 2016. Hypothesis (1, 2 and 3) was accepted